DEVELOPMENT OF MSMEs IN FISHERMAN'S WIFE GROUP PROCESSING OF SHABU SHRIMP IN GAMPONG KUALA BUGAK, EAST ACEH - Nurlina Nurlina; Safuridar Safuridar; Iqlima Azhar (Global Science Society, 2022)
Kuala Bugak Village is one of the rural areas located on the coast of Peureulak, East Aceh, where many of the residents are fishermen with their catches of fish and shrimp. Some of them have a shabu shrimp business processing and also processing salted fish. The purpose of this service activity is to increase the ability of the shabu (ebi) shrimp processing actors in inventory management, preparation of financial reports, as well as the formation of attractive and competitive packaging and logo/brand designs for shabu shrimp products in the community in Kuala Bugak Village. This activity was carried out using lecture, discussion, demonstration, direct practice and observation methods. The results of the implementation of the program that have been achieved so far are that financial accounting has been carried out by the two partners, although it is still in a very simple form; as well as an awareness of attitude from partners, although there is still reluctance to process shabu shrimp hygienically. The difficulty that is still being faced is managing the raw material supply system, because the nature of the raw material for shabu shrimp is highly dependent on season/weather conditions and sea waves.